2022
DOI: 10.1002/hep4.1924
|View full text |Cite
|
Sign up to set email alerts
|

Activated and nonactivated MSCs increase survival in humanized mice after acute liver injury through alcohol binging

Abstract: The ability of the liver to regenerate after injury makes it an ideal organ to study for potential therapeutic interventions. Mesenchymal stem cells (MSCs) possess self-renewal and differentiation properties, as well as anti-inflammatory properties that make them an ideal candidate for therapy of acute liver injury. The primary aim of this study is to evaluate the potential for reversal of hepatic injury using human umbilical cord-derived MSCs. Secondary aims include comparison of various methods of administra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…When liver tissue damage occurs, neutrophils are recruited from the peripheral blood to respond to chemokines released from the injured liver, and the infiltration of neutrophils is commonly observed, especially in mice and patients with alcoholic steatohepatitis [ 33 , 34 ]. Several studies have reported that MSCs isolated from bone marrow alleviate alcohol-induced liver injury via suppressing hepatic neutrophil and macrophage infiltration, and oxidative stress [ 35 37 ]. However, the underlying mechanism by which MSCs alleviate alcohol-induced liver injury by inhibiting hepatic neutrophil and macrophage infiltration remains unclear.…”
Section: Potential Mechanisms Of Mscs-based Therapy In Liver Diseasesmentioning
confidence: 99%
“…When liver tissue damage occurs, neutrophils are recruited from the peripheral blood to respond to chemokines released from the injured liver, and the infiltration of neutrophils is commonly observed, especially in mice and patients with alcoholic steatohepatitis [ 33 , 34 ]. Several studies have reported that MSCs isolated from bone marrow alleviate alcohol-induced liver injury via suppressing hepatic neutrophil and macrophage infiltration, and oxidative stress [ 35 37 ]. However, the underlying mechanism by which MSCs alleviate alcohol-induced liver injury by inhibiting hepatic neutrophil and macrophage infiltration remains unclear.…”
Section: Potential Mechanisms Of Mscs-based Therapy In Liver Diseasesmentioning
confidence: 99%
“… 11 In humanized mice, preconditioning MSCs with cytokines can dramatically reduce acute liver injury caused by alcohol consumption, leading to a notable improvement in both survival and hepatic function. 14 In addition, engineered MSCs can be armed as “Trojan horses” to safely deliver cytokines, including TRAIL, type I IFNs, and IL-2. 15 17 Thus, the versatile development of engineering strategies in MSC-based clinical applications contributes to strengthening innate functions (eg, immunomodulatory and regenerative properties) and expanding the therapeutic scope of MSCs, thereby maximizing clinical potency in treating diseases.…”
Section: Introductionmentioning
confidence: 99%